A gigawatt power pulsed ion beam generator for industrial applications; Surface and Coatings Technology; Vol. 228, suppl. 1 : Plasma Surface Engineering (AEPSE 2011) - Pushkarev A. I. Aleksandr Ivanovich (2013, 2013)
Title screen